2020
DOI: 10.1542/peds.2020-0083
|View full text |Cite
|
Sign up to set email alerts
|

Motor Impairment in Children With Congenital Heart Defects: A Systematic Review

Abstract: CONTEXT: With improvements in survival rates in newborns with congenital heart defects (CHDs), focus has now shifted toward enhancing neurodevelopmental outcomes across their life span. OBJECTIVE: To systematically review the prevalence and extent of motor difficulties in infants, children, and adolescents with CHD requiring open-heart surgery. DATA SOURCES: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 82 publications
0
41
0
Order By: Relevance
“…Children and adolescents with congenital heart disease (CHD) are at high risk for developmental delays. [1][2][3] These delays can affect various developmental domains, such as cognitive, language, psychosocial, and motor abilities, to different degrees based in part on the complexity of the CHD. [1][2][3][4] Although approximately 10% of children with less complex forms of CHD (eg, atrial septal defect and ventricular septal defect) experience persisting developmental impairments, delays are documented in up to 50% of the children with more complex CHD (eg, tetralogy of Fallot, coarctation of the aorta, transposition of the great arteries, and single functional ventricle).…”
Section: R Esum Ementioning
confidence: 99%
See 1 more Smart Citation
“…Children and adolescents with congenital heart disease (CHD) are at high risk for developmental delays. [1][2][3] These delays can affect various developmental domains, such as cognitive, language, psychosocial, and motor abilities, to different degrees based in part on the complexity of the CHD. [1][2][3][4] Although approximately 10% of children with less complex forms of CHD (eg, atrial septal defect and ventricular septal defect) experience persisting developmental impairments, delays are documented in up to 50% of the children with more complex CHD (eg, tetralogy of Fallot, coarctation of the aorta, transposition of the great arteries, and single functional ventricle).…”
Section: R Esum Ementioning
confidence: 99%
“…[1][2][3] These delays can affect various developmental domains, such as cognitive, language, psychosocial, and motor abilities, to different degrees based in part on the complexity of the CHD. [1][2][3][4] Although approximately 10% of children with less complex forms of CHD (eg, atrial septal defect and ventricular septal defect) experience persisting developmental impairments, delays are documented in up to 50% of the children with more complex CHD (eg, tetralogy of Fallot, coarctation of the aorta, transposition of the great arteries, and single functional ventricle). 4 Some of these developmental challenges will become evident in early childhood, but others, such as impaired executive functions and learning, become apparent only as the child gets older or during adolescence.…”
Section: R Esum Ementioning
confidence: 99%
“…Previous studies have reported that motor impairments occur in approximately one-third of all patients with CHD across infancy, childhood and adolescence (see systematic review: ( Bolduc et al, 2020 ). Infants with CHD undergoing heart surgery before the age of 6 months show noticeably delayed motor development at the age of one year with an average Psychomotor Development Index of 78 measured with the Bayley Scales of Infant Development II ( Snookes et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has become evident that children with complex CHD requiring open-heart surgery are at increased risk for neurodevelopmental impairments in various developmental domains including cognitive, behavioral and motor function. Delayed motor milestones may already appear in the first year of life ( Latal, 2016 ) and mild to moderate motor impairments often persist across childhood and adolescence ( Bolduc et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation